Relevansi Nilai Gotong Royong dalam Ajaran Pangestu sebagai Upaya Memerangi Covid 19 - Faisal Anas (Jantra., 2021)
Since the beginning of Covid-19 pandemicin Indonesia, the number of sufferers has always increased. Even by the beginning of 2021 the number has reached one million people. The government’s efforts to prevent the spread of this virus apparently through the application of health protocols seemed not to be effective. This is partly related to the egoistic behavior of the people in doing the health protocols in their daily life. In fact, the government stressed the importance of working together in the fight against Covid-19. Based on this, the author seeks to introduce the values of mutual cooperation contained in Pangestu as one of the traditional beliefs in Indonesia to people affected by Covid-19.Data were collected from the book of Pangestu, books, and any other literature about teaching of mutual cooperation. The results show that some of these values include the importance of willingly sacrificing to save others. Furthermore, the other value is togetherness and unity to obey the rules of each individual to achieve mutual salvation. By applying these values efforts to prevent the spread of Covid 19 will certainly be much more effective.